Development of Indonesian comic-based teaching materials to improve students’ creativity - Three Mutiara Sipa; Sahkholid Nasution (Inovasi Kurikulum, 2024)
This research is motivated by the decline in student creativity in participating in learning and, therefore, the need for appropriate media for students. After being given comic-based teaching materials, the activities aimed to increase students' creativity in grade IV. The research method used is research and development (Research and Development) using the ADDIE development model (Analysis, Design, Development, Implementations, Evaluation). This comic-based teaching material has undergone validation tests by experts. The percentage of results from experts on this comic-based teaching material is very valid and practical, based on criteria from media experts and material experts. In addition, the student and teacher response questionnaires also show very valid and practical criteria. From the N-gain results, a score is obtained in the high category. Therefore, this study shows the influence of using comic teaching materials to increase creativity in learning fictional story texts. It can be proven that the results show an increase from the ineffective category to the effective category. The conclusion is that this comic-based teaching material is very suitable, practical, and effective for use in learning Indonesian in fictional story texts to improve the creativity of elementary school students. AbstrakPenelitian ini dilatar belakangi oleh adanya penurunan kreativitas peserta didik dalam mengikuti pembelajaran, maka dari itu perlunya media yang tepat untuk peserta didik. Adapun kegiatan yang dilakukan ini bertujuan untuk meningkatkan kreativitas peserta didik di kelas IV setelah diberi bahan ajar berbasis komik. Metode penelitian yang digunakan adalah penelitian pengembangan (Research and Development) dengan menggunakan model pengembangan ADDIE (Analisys, Design, Develovment, Implementations, Evaluation). Bahan ajar berbasis komik ini telah melakukan uji validasi oleh ahli. Persentase hasil dari para ahli terhadap bahan ajar berbasis komik ini mendapatkan kriteria sangat valid dan sangat praktis dari ahli media dan ahli materi. Selain itu angket respons peserta didik dan angket respons guru juga menunjukkan kriteria sangat valid dan sangat praktis. Dari hasil N-gain diperoleh skor pada kategori tinggi, oleh karena itu penelitian ini menunjukkan bahwa terdapat pengaruh penggunaan bahan ajar komik untuk meningkatkan kreativitas pada pembelajaran teks cerita fiksi. Hal ini dapat dibuktikan bahwa hasil menunjukkan peningkatan dari kategori tidak efektif menjadi efektif. Adapun kesimpulannya bahwa bahan ajar berbasis komik ini sangat layak, praktis, dan efektif untuk di gunakan di dalam pembelajaran Bahasa Indonesia pada materi Teks cerita fiksi untuk meningkatkan kreativitas peserta didik sekolah dasar.Kata Kunci: bahan ajar; bahasa Indonesia; komik; kreativitas peserta didik; media pembelajaran